2001
DOI: 10.1179/107735201800339669
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function of Workers Exposed to Ammonia: A Study in the Eastern Province of Saudi Arabia

Abstract: To determine the effect of chronic exposure to ammonia on pulmonary function among ammonia workers, 77 workers were randomly selected from an ammonia factory in the Eastern Province of Saudi Arabia and 355 were selected as controls from the administrative staffs of four industrial groups in Eastern Province. Spirometry was carried out and FEV1, FVC, and FEV1/FVC% were calculated. The ammonia level in the working environment was determined spectrophotometrically. 30% of the air samples had ammonia concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
1
13
1
Order By: Relevance
“…In a soda ash plant, where the workers were exposed to the same levels of ammonia as in our swine house [9.2 SD 1.4) ppm], no difference regarding baseline lung function or workshift change was reported in a comparison with the results of a control group (37). In another study, workers in an ammonia factory were compared with a control group, and only the workers exposed to high cumulated levels of ammonia (>50 mg/m 3 annually) showed a reduced lung function (38). On the whole, there are many reports of acute human accidental exposures to inhaled ammonia, but it is difficult to find studies measuring the health effects of long-term and low-exposure concentrations of ammonia (39).…”
Section: Discussionmentioning
confidence: 91%
“…In a soda ash plant, where the workers were exposed to the same levels of ammonia as in our swine house [9.2 SD 1.4) ppm], no difference regarding baseline lung function or workshift change was reported in a comparison with the results of a control group (37). In another study, workers in an ammonia factory were compared with a control group, and only the workers exposed to high cumulated levels of ammonia (>50 mg/m 3 annually) showed a reduced lung function (38). On the whole, there are many reports of acute human accidental exposures to inhaled ammonia, but it is difficult to find studies measuring the health effects of long-term and low-exposure concentrations of ammonia (39).…”
Section: Discussionmentioning
confidence: 91%
“…The remaining 10 studies described irritant-induced OA cases [235,423-426,530] or identified significant asthma symptoms/ obstructive ventilation patterns without a clear diagnosis (5 studies: [178,417,420,556]). It can be assumed that if it had been considered on the other 10 studies then occupational COPD caused by cement dust would have been frequently observed.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term exposure to lower levels has been associated with sinusitis, mucous membrane inflammation syndrome, chronic bronchitis, and asthma-like symptoms 19 ) . Results of a cross-sectional study showed that chronic exposure to high cumulative concentrations of ammonia (>70 ppm-yr) compared to lower cumulative exposure levels (≤70 ppm-yr) significantly reduced some parameters of pulmonary function such as FEV1 and FVC 16 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary effects of short and long term exposure to high atmospheric concentrations of ammonia have been well documented 11 , 12 , 13 , 14 , 15 , 16 , 17 ) .…”
Section: Introductionmentioning
confidence: 99%